2019
DOI: 10.1088/1742-6596/1359/1/012077
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of turbulent Rayleigh-Bénard mercury convection in a circular cylinder with introducing small deviations from the axisymmetric formulation

Abstract: Results of DNS are reported for turbulent Rayleigh-Bénard mercury convection (Pr = 0.025) in a cylindrical container with the aspect ratio of unity at the Rayleigh number of Ra = 106. The main goal of the study is to estimate the influence of small deviations from the axisymmetric formulation on the behavior of large-scale circulation (LSC) developing in the container. The deviations examined are a small tilt of the cylinder or prescribed sinusoidal disturbances of the bottom wall temperature. The effects of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Thus for both cases the cell size exceeded the minimum turbulence scale only within the restricted areas of the regions, and at the most by factor 2. In our previous studies [37,38], it was shown that such degree of resolution of the turbulent content is sufficient to obtain grid-independent fields of average velocity and temperature, as well as pulsation values characterizing small-scale turbulence (this will also be illustrated in the present study).…”
Section: Computational Aspectssupporting
confidence: 59%
See 2 more Smart Citations
“…Thus for both cases the cell size exceeded the minimum turbulence scale only within the restricted areas of the regions, and at the most by factor 2. In our previous studies [37,38], it was shown that such degree of resolution of the turbulent content is sufficient to obtain grid-independent fields of average velocity and temperature, as well as pulsation values characterizing small-scale turbulence (this will also be illustrated in the present study).…”
Section: Computational Aspectssupporting
confidence: 59%
“…The coordinate system has its origin in a center of the cylinder. Some details on the problem definition, as well as preliminary results, were reported by us in [37,38]. No-slip conditions are imposed on all boundaries.…”
Section: Rayleigh-bénard Convection In a Cylindermentioning
confidence: 99%
See 1 more Smart Citation